Stepping Out. - CHAN, MICHELE (ArtAsiaPacific)
The article focuses on Kiang Malingue, a contemporary art gallery co-owned by Lorraine Kiang and Edouard Malingue, which recently opened a new location in New York City. The gallery aims to showcase innovative multimedia artists, particularly from Asia, and has a history of promoting emerging talents who have gained international recognition. The owners emphasize their commitment to presenting art in engaging environments that encourage visitor interaction, moving away from the traditional white cube gallery model. They express a desire to focus on artistic practices rather than conforming to identity-based categorizations of artists.